PERBANDINGAN EFEKTIVITAS ASAM MEFENAMAT, PARASETAMOL, DAN IBUPROFEN DALAM PENGELOLAAN NYERI KEPALA PRIMER PADA MAHASISWA KEDOKTERAN - Daswara Djajasasmita; Rhea Veda Nugraha; Anfika Azhari (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Primary headache is a common neurological complaint among medical students, often associated with academic stress, sleep deprivation, and unhealthy lifestyle patterns. Over-the-counter analgesics such as mefenamic acid, paracetamol, and ibuprofen are frequently used for self-medication; however, comparative data regarding their effectiveness in this population remain limited. This study aimed to compare the effectiveness of these three drugs in the management of primary headache among medical students. This study employed an analytical cross-sectional design involving 73 students from the Faculty of Medicine, Universitas Jenderal Achmad Yani, class of 2024. Data were collected using questionnaires assessing the type of analgesic used, onset of action, and duration of effect, and were analyzed using the Kruskal–Wallis test. Most respondents were classified as having probable migraine (61.7%) based on the HSQ. Paracetamol was the most commonly used analgesic (75.3%), followed by ibuprofen (9.9%) and mefenamic acid (4.9%). The fastest onset of action (<30 minutes) was most frequently reported with mefenamic acid (75%), while the longest duration of effect (>8 hours) was mainly observed with ibuprofen and mefenamic acid (25% each). However, no statistically significant differences were found in onset of action (p = 0.472) or duration of effect (p = 0.060) among the three drugs. These findings indicate that the three analgesics demonstrate comparable effectiveness in relieving primary headache among medical students. The observed differences appear to represent clinical tendencies rather than statistically significant variations. Keywords: ibuprofen, medical student, mefenamic acid, paracetamol, primary headache DOI : 10.35990/mk.v9n1.p79-90